2011
DOI: 10.2174/187152011795347450
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative Activity of Synthetic Ajoene Analogues on Cancer Cell-Lines

Abstract: The ability of garlic preparations to inhibit cancer cell-growth has been attributed to a group of structurally-related organosulfur compounds found in the crushed clove. Historically, interest has centred on three such compounds as allicin, diallyl disulfide and diallyl trisulfide, with less interest on E- and Z-ajoene. A recently developed synthetic route from our laboratory for preparing ajoene analogues allows access to derivatives containing the sulfoxide / vinyl disulfide core whilst varying the terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…Garlic has been used as a home remedy for a myriad of diseases for thousands of years. To date, garlic and its constituents are known to have many beneficial attributes such as antimicrobial (Casella et al, 2013;Goncagul and Ayaz, 2010), antiatherosclerotic (Asdaq et al, 2009;Chan et al, 2013;Gonen et al, 2005;Malekpour-Dehkordi et al, 2013), antitumorigenetic (Iciek et al, 2009;Kaschula et al, 2011), and immunomodulatory (Iciek et al, 2009) properties. Of particular interest for our studies is the modulation of cytokine production by garlic as cytokines are important immune system mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Garlic has been used as a home remedy for a myriad of diseases for thousands of years. To date, garlic and its constituents are known to have many beneficial attributes such as antimicrobial (Casella et al, 2013;Goncagul and Ayaz, 2010), antiatherosclerotic (Asdaq et al, 2009;Chan et al, 2013;Gonen et al, 2005;Malekpour-Dehkordi et al, 2013), antitumorigenetic (Iciek et al, 2009;Kaschula et al, 2011), and immunomodulatory (Iciek et al, 2009) properties. Of particular interest for our studies is the modulation of cytokine production by garlic as cytokines are important immune system mediators.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far the best characterized naturally occurring H 2 S-donating compound from garlic ( Allium sativum ) is allicin (diallyl thiosulfinate) which decomposes in water to a number of compounds [56]. Benavides et al [57] measured H 2 S production in real time with a polarographic sensor and observed that under anoxic conditions and in the presence of GSH, red blood cells rapidly (within minutes) produced H 2 S from garlic extract as well as from two of the decomposition products of allicin, diallyl disulfide (DADS) and diallyl trisulfide (DATS; Fig, 2A), with approximately 3 times the yield from the latter.…”
Section: H2s “Donating” Compoundsmentioning
confidence: 99%
“…Garlic reduces the side effects caused by anti-cancer agents. Thus, garlic and garlic-derived compounds are promising candidates for breast cancer cont ility of garlic preparations to inhibit cancer cell-growth has been attributed to a group of structurally-related organosulfur compounds found in the crushed clove [103]. For many years, in vitro and in vivo studies have reported that organosulfur compounds (OSCs), naturally found in Allium vegetables are able to suppress the proliferation of various tumor cells.…”
Section: Garlicmentioning
confidence: 99%